2018
DOI: 10.3390/ijms19061815
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mechanism of Inhibition of Au Nanoparticles on the Aggregation of Amyloid-β(16-22) Peptides at the Atom Level by All-Atom Molecular Dynamics

Abstract: The abnormal self-assembly of the amyloid-β peptide into toxic β-rich aggregates can cause Alzheimer’s disease. Recently, it has been shown that small gold nanoparticles (AuNPs) inhibit Aβ aggregation and fibrillation by slowing down the nucleation process in experimental studies. However, the effects of AuNPs on Aβ oligomeric structures are still unclear. In this study, we investigate the conformation of Aβ(16-22) tetramers/octamers in the absence and presence of AuNPs using extensive all-atom molecular-dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 49 publications
1
15
0
1
Order By: Relevance
“…MD simulations have also been used to investigate the inhibition process of amyloid β (Aβ) fibrillation by using Au-NPs [546]. The simulations showed that Au-NPs can influence the conformational change of the peptides and reduce inter-peptide interactions which can in turn prevent the β-Sheet formation of Aβ peptides and prolong the progress of Aβ aggregation.…”
Section: Interactions With Viruses and Biomacromoleculesmentioning
confidence: 99%
“…MD simulations have also been used to investigate the inhibition process of amyloid β (Aβ) fibrillation by using Au-NPs [546]. The simulations showed that Au-NPs can influence the conformational change of the peptides and reduce inter-peptide interactions which can in turn prevent the β-Sheet formation of Aβ peptides and prolong the progress of Aβ aggregation.…”
Section: Interactions With Viruses and Biomacromoleculesmentioning
confidence: 99%
“…Hydrophobic interactions play important roles between the inhibitors and the residues of SIRT6. In previous computer simulation studies, hydrophobic interactions between small molecules and proteins have also been reported [44][45][46][47][48].…”
Section: Resultsmentioning
confidence: 88%
“…∆G polar is calculated by the GB model [64] and ∆G suf is estimated by the solvent accessible surface area (SASA). As the binding energy (∆G binding ) reported here is the relative binding free energy, the contribution of conformational entropy of the small molecule was ignored in accordance with a number of previous computational studies [45,46,66,67]. Therefore, in this study, we use the formula ∆G binding = ∆E MM + ∆G solv [61] to calculate the binding free energy.…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Gold complexes may inhibit the aggregation of amyloid peptides mainly by metal coordination [ 95 , 130 ]. Some Au complexes showed good inhibitory effects on amyloid peptides, such as PrP106–126, hIAPP, and Aβ protein [ 94 , 131 , 132 , 133 ].…”
Section: Metal Binding Sites In Amyloid Oligomers and Their Polymementioning
confidence: 99%